Hierarchical categorization of characters in classic Hollywood cinema (Research, Society and Development, 2023)
The object of this paper is the analysis of the construction of characters in classic Hollywood cinema, focusing on the identification of characters with leading roles. The aim is to identify trends in the creation of characters in classic cinema and how these trends are influenced by film genres. It is based on the hypothesis that the leading roles fulfill very precise functions in the story. The main objective is to identify the functions that the characters must fulfill in classic Hollywood cinema to be considered protagonists, using precise and contrasted indicators. This work applies a narrative analysis methodology based on audiovisual textual analysis, based on the phenomenological analysis of the character. A sample of 80 paradigmatic films of the cinematographic practice analyzed is taken. It can be concluded that in classic cinema one of the characters focuses and organizes the story, has exclusive functions and has a greater number of data that define it. The presence of a single protagonist, identified in the film with a specific individual, allows the acquisition of unity and internal cohesion of the narrative, thereby fulfilling the basic objective of unity of traditional drama.